Inositols: pharmacology and findings of clinical trials. Current evidence and prospects - Yu.E. Dobrokhotova; O.A. Gromova; A.S. Dukhanin; Z.Kh. Kumykova; E.V. Sheremetyeva; G.I. Tabeeva (LCC «Medicine-Inform», 2022)
Yu.E. Dobrokhotova1, O.A. Gromova2, A.S. Dukhanin1, Z.Kh. Kumykova3, E.V. Sheremetyeva4, G.I. Tabeeva3 1Pirogov Russian National Research Medical University, Moscow, Russian Federation 2Federal Research Center "Informatics and Management" of the Russian Academy of Sciences, Moscow, Russian Federation 3V.I. Kulakov National Medical Research Center for Obstetrics, Gynecology and Perinatology, Moscow, Russian Federation 4National Medical Research Center of Endocrinology, Moscow, Russian Federation Alterations in reproductive functions are associated with metabolic disorders, eating habits and lifestyle. In this context, a growing body of research is currently focused on the use of various vitamins and vitamin-like substances, such as inositol, in female patients with alterations in reproductive functions and metabolic disorders. Co-administration of inositol with pathogenetic therapy can be recommended to women of reproductive age with metabolic syndrome, as an additional option for preserving fertility and activating ovarian functions in young female patients with diminished ovarian reserve. Myoinositol and D-chiroinositol are inositol stereoisomers demonstrating the highest metabolic activity. The beneficial ratio of Myoinositol (MI) to D-chiroinositol (DCI) ensures the healthy state of organs and tissues, while a misbalance or depletion of inositol levels can cause various diseases. Combination of MI and DCI in a 5:1 ratio with manganese and folic acid is an  original non-hormonal formula designed to improve functional state of the female reproductive system as well as carbohydrate and lipid metabolism. In addition, this combination should be considered as a promising alternative for the management of metabolic disorders in perimenopausal women. Keywords: reproductive function, metabolism, inositol, myoinositol, D-chiroinositol, polycystic ovary syndrome, ovarian reserve, menopause, metabolic syndrome, manganese, folic acid. For citation: Dobrokhotova Yu.E., Gromova O.A., Dukhanin A.S. et al. Inositols: pharmacology and findings of clinical trials. Current evidence and prospects. Russian Journal of Woman and Child Health. 2022;5(4):309-319 (in Russ.). DOI: 10.32364/2618-8430-2022-5-4-309-319.